Cultural implications of knowledge sharing, management and transfer : identifying competitive advantage - Harorimana, Deogratias, 1972- (Hershey, PA : Information Science Reference, 2010)
'This book illustrates, compares, and discusses models, perspectives, and approaches involved in the distribution, administration, and transmission of knowledge across organizations'--Provided by publisher.
'Premier reference source'--Cover.
Includes bibliographical references and index.
Keywords: Knowledge management; Knowledge management -- Social aspects